The relationship between pregnancy stress and mental health of the pregnant women: the bidirectional chain mediation roles of mindfulness and peace of mind - Sun, Shasha; Luo, Chunqi; Zeng, Xun; Wu, Qichang (Frontiers in Psychology, 2024)
The relationship between pregnancy stress and mental health of the pregnant women: the bidirectional chain mediation roles of mindfulness and peace of mindObjective: This study aimed to investigate the relationship between pregnancy stress and mental health of the pregnant women, employing a positive psychology perspective. Specifically, the study sought to explore how the two positive psychological qualities of mindfulness and peace of mind may serve as potential mediators in the association between pregnancy stress and mental health of the pregnant women.Methods: Seven hundreds and thirteen pregnant women seeking care at the First Affiliated Hospital of Sun Yat-Sen University were included in this study. The participants completed a self-report demographic questionnaire, as well as several validated scales including the Pregnancy Pressure Scale (PPS), Mindful Attention Awareness Scale (MAAS), Peace of Mind Scale (PoMS), and Chinese Health Questionnaire (CHQ). The Amos 23.0 system was utilized to construct structural equation models.Results: A total of 713 participants had an average age of 29.46 ± 4.81 years and an average gestational age of 24.26 ± 22.66 weeks. Out of the pregnant women, 163 (22.9%) experienced moderate or higher levels of pregnancy stress (PPS > 1), while 212 (29.7%) exhibited mental distress (CHQ > 3). Pregnancy stress exhibited a positive association with mental distress, while displaying negative associations with mindfulness and peace of mind. Mindfulness and peace of mind were negatively associated with mental distress. By employing structural equation modeling, the analysis revealed that mindfulness and peace of mind acted as partial mediators in the relationship between pregnancy stress and mental health. Furthermore, the identified models exhibited bidirectional sequential mediating pathways, suggesting that the pathways of mindfulness ↔ peace of mind mitigated the harmful influence of pregnancy stress on the mental health of pregnant women.This study adds to the current body of knowledge by investigating the relationships among mindfulness, peace of mind, pregnancy stress, and mental health in pregnant women. From a positive psychology framework, it provides valuable understanding of the intricate dynamics between pregnancy stress and protective factors of mental health.